Sistem Pendukung Keputusan Untuk Menentukan Rekomendasi Wisata Dengan Menggunakan Metode Profile Matching dan SMART - Ivang Fahmi Fauzi; Alam Rahmatulloh; Andi Nurachman (LPPM Universitas Perjuangan Tasikmalaya, 2020)
Empirically tourism has shown increasing growth marked by an increase in the frequency of people who travel. Tourism activities create many benefits including the spread of development, foreign exchange earnings, regional income through tax collection, employment and creating business opportunities. The problem that often arises is that there are still many people who travel, but instead it creates new thoughts. Traveling is also an important physical need without us knowing. One of the decision-making problems faced with various criteria is the process of selecting tourist attractions. In the process of profile matching in broad outline is the process of comparing the competency of visitors into the competence of tourist attractions so that the competency differences can be known (also called a gap), the smaller the gap produced, the greater the value weights which means it has a greater chance for the priority of certain tourist attractions chosen by tourists (visitors). While the SMART (Simple Multi-Attribute Rating Technique) method is a multi-criteria decision making method. This multi-criteria decision making technique is based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that illustrates how important compared to other criteria. Each tourism object has the value of road access criteria, facilities, prices and visitors from the results of the previous profile matching calculation, then the weight normalization calculation from the simple multi attribute rating method is calculated and summed to find out the final score results, and then descending. From the results, the selection of suitable tourism object is very objective because it has fulfilled the assessment of each criteria.